School as stakeholder of corporate social responsibility program: teachers perspective on outcome in school development - Ismail, Maimunah; Amat Johar, Ratna Fauzi; Mohd Rasdi, Roziah; Alias, Siti Noormi (Springer, 2014)
Knowledge of the outcome of corporate social responsibility (CSR) programs in school development in developing countries such as Malaysia is limited. This article examines types of CSR programs and the outcome on school development from the perspective of teachers. Data from a survey involving 273 teachers of schools that have participated in CSR programs, and data from focus group discussions with two groups of teachers were used in the analyses. The results of this exploratory study show that schools gained most from CSR programs in terms of improvement in the schools’ physical infrastructure and facilities through funds provided, followed by provisions of reading materials for students and teachers in these programs. The results also revealed that the CSR programs contributed significantly to school development in terms of school living, student achievement, and school achievement.